Emic and Etic Perspectives on HR Practice for Managing Human Resource Issues Affected by the Prevalence of Informal Networks in Arab Countries - Sa’ad Ali; David Weir; Munirah Sarhan AlQahtani; Mansour Mrabet (Administrative Sciences)
Whilst research on Wasta has been improving in quantity and quality, there is still much more to know about the interactions between the different parties in Wasta transactions, the role of power in this process and how it impacts HR functions. As such, this research aims to address this gap by exploring the use of Wasta in human resources (HR) functions, drawing on 17 semi-structured interviews with HR, recruitment and line managers working in the Jordanian banking sector. This paper focuses on the roles of trust and power in the organizational transactions in which Wasta is positioned and identifies recruitment and selection (R&S) as one of the main human resource (HR) practices and procedures that are affected by Wasta. The findings shed light on the impact of Wasta on HRM practice on the micro and macro levels, highlighting the complex socio-economic needs for this practice which, whilst they might be beneficial on the micro level in terms of securing employment for job seekers and benefits for organizations in the Wasta exchange process, can also have some substantive negative outcomes in the forms of social and economic exclusion of others outside the Wasta network. By doing so, it develops the conceptualization beyond the often-simplistic view of Wasta as a negative (and sometimes positive) practice as viewed by previous research extending it to a practice that could have either impact on different stakeholders.